The Impact of Palm Oil Industry Development on Indonesian Palm Oil and Palm Kernel Oil Exports In 2012–2021 - Rianto, Rio; Lumbanraja, Pretty Luci; Lumbanraja, Penny Chariti (Universitas Djuanda, 2025)
The Indonesian palm oil industry is growing rapidly and has promising prospects as a major contributor to the country's foreign exchange. Optimizing the palm oil industry's contribution to state revenue is crucial, given that the sector's substantial potential remains untapped due to weak downstream processing, dependence on global prices, and ineffective fiscal policies. This research aims to provide an empirical basis for formulating strategies to sustainably increase the added value and competitiveness of the national palm oil industry. This study aims to analyze the impact of palm oil industry development on state revenues derived from crude palm oil (CPO) and palm kernel oil (PKO) exports for the 2012–2021 period. The analysis method uses the Structural Equation Modeling – Partial Least Square (SEM-PLS) approach with industry development indicators including fresh fruit bunch prices, investment realization, wages/salaries, production volume, and the number of plantation companies. The results show that palm oil industry development has a positive but insignificant impact on state revenues, with a significance value of 0.118 (> 0.05) and an influence coefficient of 0.692. These findings indicate that the vast potential of the palm oil industry has not yet fully contributed optimally to state revenues. The main contributing factors include dependence on fluctuating global prices, suboptimal fiscal and export policies, weak downstreaming, and limited added value of derivative products. The implication is that improvement strategies are needed, including rejuvenating smallholder oil palm plantations, accelerating ISPO certification, strengthening downstream processing, developing a cross-sector national palm oil roadmap, providing supporting infrastructure, developing human resources, and fostering more sustainable governance. These efforts are expected to increase the competitiveness of the palm oil industry and increase its contribution to state revenue.